GSM based door open and closing system - Usha, V; Rajkumar, N; M. Shyamala Devi, Dr; Saranya Jothi, C (International Journal of Engineering and Technology, 2018)
GSM based Door Access Security System has principle application in security frameworks and it can be utilized as a part of Industries, Shops, Offices and in our homes. It replaces the customary security frameworks which utilizes key to open entryway. This venture has keyless passage to the entryway. Client needs to send secret key through SMS utilizing his/her portable. In the event that the secret key is right then Microcontroller turns on a DC engine and a Relay. Bell is turned on for wrong secret key. In its most straightforward shape Home security is the capacity to control entryway open or close Family security remotely. The transmitter depends on remote GSM strategy the idea Door bolting and opening System utilizes GPRS to open and close the entryway. Not with standing this security will be given utilizing GSM in the event of any unapproved get to. DC engine will then perform activity on entryway either bolting or opening.
Keywords: SMS; DC; GPRS; GSM; Door access security system